2017
DOI: 10.1186/s12917-017-1122-4
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of avian leukosis virus subgroup J (ALV-J) from hens infected through artificial insemination with ALV-J infected semen

Abstract: BackgroundAvian leukosis virus (ALV) is one of the main causes of tumour development within the poultry industry in China. The subgroup J avian leukosis viruses (ALV-J), which induce erythroblastosis and myelocytomatosis, have the greatest pathogenicity and transmission ability within this class of viruses. ALV can be transmitted both horizontally and vertically; however, the effects of ALV infection in chickens—especially roosters—during the propagation, on future generations is not clear. Knowing the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Among the latter, subgroups A, B and K mostly occur in indigenous chicken breeds with rare reports concerning subgroups C and D 4 , 14 , 26 , 27 , while ALV-J, being capable of inducing severe tumors and related symptoms in chicken, used to be the main cause of AL outbreak in commercial broilers and layers 28 , 29 . As a virus mainly spread vertically 30 , ALV can be controlled by strict provenance eradication measures, which has been carried out in many commercial flocks and achieved great achievements in a lot of countries 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, subgroups A, B and K mostly occur in indigenous chicken breeds with rare reports concerning subgroups C and D 4 , 14 , 26 , 27 , while ALV-J, being capable of inducing severe tumors and related symptoms in chicken, used to be the main cause of AL outbreak in commercial broilers and layers 28 , 29 . As a virus mainly spread vertically 30 , ALV can be controlled by strict provenance eradication measures, which has been carried out in many commercial flocks and achieved great achievements in a lot of countries 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Li previously found that ALV-J in semen could be transmitted to hens by insemination through animal experiments in SPF chicken [13], but they only discovered the antibody of ALV-J, without viraemia in the hens and their offspring. This study is based on the infected clinical ocks.…”
Section: Discussionmentioning
confidence: 99%
“…Rubin and his colleagues de ned four serological classes of susceptible birds: viraemia, no antibody (V + A−); no viraemia, with antibody (V − A+); viraemia, with antibody (V + A+); and no viraemia, no antibody (V − A−) [2,12]. Another study showed that roosters could spread ALV-J to hens by insemination and cause vertical transmission [13]. Yet the researchers did not elaborate on the ALV infection status of semen from male or the role of males in the transmission of ALV.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is absolutely imperative that the strategies should be implemented to prevent and control ALV-J infection in poultry industry. Attributed to the implementation of ALV-J eradication program (6), there were rarely reports of ALV-J or myelocytomatosis in China after 2013. Nevertheless, there were another intensive reports about ALV-J breakout almost simultaneously in six provinces of China in 2018, which attracted our attention (7).…”
Section: Introductionmentioning
confidence: 99%